2018
DOI: 10.1016/j.solener.2018.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Fully bio-originated latent heat storing calcium alginate microcapsules with high coconut oil loading

Abstract: Latent heat storing calcium alginate microcapsules were manufactured by a repeated interfacial coacervation/crosslinking method. By using a high-viscosity sodium alginate for the capsule formation, the paraffin phase change material (PCM) content was substantially enhanced related to the recently developed procedure. The maximization of PCM loading was achieved using experimental design for paraffin containing microcapsules. The microcomposites were optimized for 81.5 % PCM content with uniform size of 2.20 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…18 Recently, entirely eco-friendly microparticles were prepared by a scaled-up procedure using the same shell material, however, encapsulating coconut oil. 19 These fully bio-originated microcapsules possessed high PCM content (81.1% m/m) together with compact shell. Ca alginate is supposed to have antimicrobial effect, however, we experienced that subjecting it to water, our microcapsules were infected by mildew within some weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Recently, entirely eco-friendly microparticles were prepared by a scaled-up procedure using the same shell material, however, encapsulating coconut oil. 19 These fully bio-originated microcapsules possessed high PCM content (81.1% m/m) together with compact shell. Ca alginate is supposed to have antimicrobial effect, however, we experienced that subjecting it to water, our microcapsules were infected by mildew within some weeks.…”
Section: Introductionmentioning
confidence: 99%
“…In our group a novel method was developed to use Ca alginate to entrap paraffin PCM in order to obtain core‐shell microcapsules with high heat storing capacity 18 . Recently, entirely eco‐friendly microparticles were prepared by a scaled‐up procedure using the same shell material, however, encapsulating coconut oil 19 . These fully bio‐originated microcapsules possessed high PCM content (81.1% m/m) together with compact shell.…”
Section: Introductionmentioning
confidence: 99%
“…There are no reports assessing margarine and shortening as potential PCMs in terms of their thermal properties and their thermal stabilities, and only a few studies reporting the thermal properties of coconut oil and its application as a PCM for TES [25,26,[29][30][31][32][33][34][35]. The latter showed that coconut oil could be useful for TES in buildings, given that its transition temperature is between 22 and 27 • C [25,26,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The third weight loss stage starting from 350 °C to 730 °C is the decomposition of both SA and sodium carbonate [ 24 , 25 ]. The residue of SA is 30.8%, corresponding to the formed carbon dioxide and calcium oxide [ 26 ]. Thermal degradation of gelatin occurs in two stages (curve b in Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%